Perbedaan Peran Gender dalam Tradisi Suraan pada Masyarakat Adat Cireundeu - Bagio Alief; Aafiyah Hanuun; Dewi Ayu Hidayati; Feby Afri Yulindra; Rista Aulya Panestika; Sopfi Putri Marlina (Wacana Publik, 2022)
The Suraan tradition is a tradition to commemorate one sura performed by the Cireundeu community. This tradition of one sura is an expression of gratitude to the Almighty Creator for all the blessings and gifts, blessings in life as well as physical and mental health given by Him for the sake of survival. This study aims to look at the differences in gender roles in the suraan tradition in the Cireundeu community. Gender role analysis is not only aimed at biological matters, but can also be seen from the gender relations used in a society. This research was conducted using a qualitative approach with data collection techniques in the form of interviews and documentation conducted in the Cireundeu Traditional Village, Leuwigajah Village, Cimahi Selatan District, Cimahi City with several traditional leaders as informants. speech in the Cireundeu Traditional Village community.